Avaliação da indexação em catálogos de bibliotecas universitárias por meio da recuperação da informação - Piovezan, Luciana Beatriz [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Whereas the subject indexing process as a method of knowledge organization and representation and the subject indexing policy, as a philosophy regulating the performance of indexing by providing guidelines that aim to make the information system most efficient, this dissertation has as its theme the evaluation of subject indexing in university libraries' catalogs. Given the imperative of an agenda that puts into practice and in the routine of information units the performing of evaluation studies of the process and product of subject indexing, we had as research problem the need to investigate such issues, specifically in the context of academic libraries, given the necessary avant garde characteristic of these organizations on issues of information. Thereby, the proposition was to perform comparative evaluation of subject indexing performed in catalogs of systems of academic libraries using the method of extrinsic evaluation through consistency. The aim was to contribute to studies concerning the practice of subject indexing and subject indexing evaluation in the context of knowledge organization on Information Science and the specific goals were to perform theoretical and methodological study on subject indexing and subject indexing evaluation in the field of knowledge organization and placing them in the context of academic libraries; to apply comparative study evaluating the subject indexing performed in two catalogs of systems of academic libraries and analyze the consistency of indexing as indicators of the quality of subject indexing in catalogs of systems of academic libraries. In order to do so, carried out a review of national and international literature on these topics as well as about the current context of academic libraries and applied comparative study of the subject indexing performed on two catalogs, using the method of extrinsic evaluation through consistency. The results found a strict consistency index of 24,88% and...

Considerando o processo de indexação como método de organização e representação do conhecimento e a política de indexação, enquanto uma filosofia que rege a realização da indexação ao oferecer diretrizes que visam tornar o sistema de informação mais eficiente, tem como tema a avaliação da indexação em catálogos de bibliotecas universitárias. Diante do imperativo de uma agenda que coloque em prática e no cotidiano das unidades de informação a realização de estudos avaliativos do processo e do produto da indexação, tem como problema a necessidade de averiguar tais questões, especificamente no âmbito das bibliotecas universitárias, dada a necessária característica vanguardista destas organizações nas questões de informação. Dessa forma, teve como proposição realizar avaliação comparada da indexação em catálogos online de sistemas de bibliotecas universitárias com utilização do método de avaliação extrínseca mediante a interconsistência. Teve como objetivo geral contribuir com os estudos acerca da prática da indexação e de avaliação da indexação no contexto da organização e representação do conhecimento em Ciência da Informação e como objetivos específicos realizar estudo teórico e metodológico sobre indexação e avaliação da indexação no domínio da organização e representação do conhecimento e situando-os no contexto das bibliotecas universitárias; aplicar estudo comparativo de avaliação da indexação realizada em catálogos online de dois sistemas de bibliotecas universitárias; e analisar a consistência enquanto indicador de qualidade da indexação em catálogos online de sistemas de bibliotecas universitárias. Para tanto realizou revisão de literatura nacional e internacional sobre a temática da indexação e sobre estudos de avaliação da indexação, por seu processo e seus resultados, bem como, a respeito do contexto atual das bibliotecas universitárias...
Keywords: Indexação; Política de indexação; Bibliotecas universitárias; Academic libraries